Ivabradine Treatment Reduces Cardiomyocyte Apoptosis in a Murine Model of Chronic Viral Myocarditis - Li-Sha, Ge; Li, Liu; De-Pu, Zhou; Zhe-Wei, Shi; Xiaohong, Gu; Guang-Yi, Chen; Jia, Li; Jia-Feng, Lin; Maoping, Chu; Yue-Chun, Li (Frontiers in Pharmacology, 2018)
This study was designed to explore the effects of ivabradine on cardiomyocyte apoptosis in a murine model of chronic viral myocarditis (CVMC). Mice were inoculated intraperitoneally with Coxsackievirus B3 at days 1, 14, and 28, respectively. On day 42, the mice were gavaged with ivabradine for 30 days until the 72nd day. The heart of infected mice was dilated and a large number of interstitial fibroblasts infiltrated into the myocardium on day 42. Compared with the untreated CVMC mice, mice treated with ivabradine showed a significant reduction in heart rate and less impairment of left ventricular function on day 72. The positive apoptosis of myocardial cells in the untreated CVMC group was significantly higher than that of the normal group and was significantly reduced after treatment with ivabradine. The expression levels of Bax and Caspase-3 in the untreated CVMC group were significantly higher than those of the normal group and were apparently reduced in the ivabradine-treated group versus the untreated CVMC group. Bcl-2 showed a high expression in the normal group and low expression in the untreated CVMC group, but its expression level in the ivabradine-treated group were higher than that of the untreated CVMC group. These results indicate that ivabradine could attenuate the expression of Caspase-3 by downregulation of Bax and upregulation of Bcl-2 to prevent the deterioration of cardiac function resulting from ventricular myocyte loss by cardiomyocyte apoptosis.